Adsorption of Ni(II) and Cu(II) by Thionyl Chloride and Ethylene-1,2-diamine Modified Coir Fibres - Song, Jun; Xu, Xingzhi; Dai, Xiaoli; Yang, Yaling; Liu, Mousheng (Asian Journal of Chemistry, 2011)
This study describes the preparation of a new adsorbent for heavy metal ions removal derived from coir fibres. Coir fibres was activated by using thionyl chloride and reacted with ethylene- 1,2-diamine in order to obtain modified coir fibres. Adsorption behaviours of coir fibres and modified coir fibres for Ni2+ and Cu2+ were studied respectively and the capacity of modified coir fibres to adsorb Ni2+ and Cu2+ from aqueous single metal ion solutions was evaluated at different contact times, pHs and initial metal ion concentrations. The characteristics of coir fibres and modified coir fibres were determined by SEM, XPS and FTIR techniques. The results showed that modified coir fibres had a porous and loose surface covered with amino groups, which helpful for removing Ni2+ and Cu2+ from wastewater. In the range of the designed experiments, modified coir fibres and coir fibres can reach its maximum saturated adsorption capacity (Qmax) of 0.773 mmol/g and 0.096 mmol/g for Ni2+; 1.658 mmol/g and 0.392 mmol/g for Cu2+, respectively. When the Ni2+ and Cu2+ adsorbed on modified coir fibres was desorbed by HCl, which showed high desorption efficiency, the optimum concentration of HCl was about 0.15 mol/L and the proper contact time was 20 min. In sequential adsorption and desorption cycles, the heavy metal ions uptake capacity on modified coir fibres was relatively maintained through cycles 1-5.